Microbial diversity and their extracellular enzyme activities among different soil particle sizes in mossy biocrust under N limitation in the southeastern Tengger Desert, China - Duan, Xiaomin; Li, Jiajia; He, Wangping; Huang, Jingjing; Xiong, Wanxiang; Chi, Shijia; Luo, Siyuan; Liu, Jianli; Zhang, Xiu; Li, Jingyu (Frontiers in Microbiology, 2024)
Mossy biocrust is represents a stable stage in the succession of biological soil crust succession in arid and semi-arid areas, and provides providing a micro-habitat for that maintaining maintains microbial diversity. However, the effect impact of mossy biocrust rhizoid soil and different particle sizes of within the mossy biocrust layer and sublayer soil on microbial diversity and soil enzyme activities are remains unclear. This study used utilized Illumina MiSeq sequencing and high-throughput fluorometric technique to assessdetermine the differences of in microbial diversity and soil extracellular enzymes between mossy biocrust rhizoid soil and different particle sizes of within the mossy biocrust sifting and sublayer soil. The results revealedshowed that the total organic carbon (TOC), total nitrogen (TN), ammonium (NH4 + ) and nitrate (NO3 -) in mossy biocrust rhizoid soil were the highest, with significantly higher TOC, TN and total phosphorus (TP) in mossy biocrust sifting soil were significantly higher than thatto those in mossy biocrust sublayer soil. The activities of EAAs exhibited different responses to various soil particle sizes in mossy biocrust. BRS showed higher Cdegrading enzyme activity and lower P-degrading enzyme activity, leading to a significant increase in enzyme C: P and N: P ratios. Mossy biocrust soils were all limited by microbial relative nitrogen, while pronounced relative nitrogen limitation and microbial maximum relative carbon limitation in BRS. Mossy biocrust rhizoid soil and different soil particle sizes of mossy biocrust sifting soil were affected by microbial relative N limitation, and mossy biocrust rhizoid soil was limited by the maximum microbial relative C. The diversity and richness of the bacterial community in the 0.2mm mossy buicrust soil (BSS0.2) were notably lower than those in mossy biocrust sublayer, whereas the diversity and richness of the fungal community in the rhizoid soil were significantly higher than those in mossy biocrust sublayer. The predominant bacterial phyla in mossy biocrust were Actinobacteriota,